Implementasi Pengelolaan Keuangan Masjid Agung Asy Syuhada Pamekasan Berdasarkan PSAK No.45 Tentang Pelaporan Keuangan Organisasi Nirlaba - Hidayat, Moh. Nurul; Priyadi, Ira Hasti (Shafin: Sharia Finance and Accounting Journal, 2022)
The mosque is a non-profit organization that must and has the right to make reports and report them to the users of interested parties. The financial statements of non-profit organizations different from the financial statements of business organizations in general, one of the main differences lies in the form of financial statements. The financial statements of non-profit organizations that contain funds or donations from various parties that must be accounted for by management to internal parties and external parties.Presentation of adequate financial statements and in accordance with generally accepted standards in Indonesia, namely PSAK No. 45 on Financial Reporting of Non-Profit Organizations. Standards are created to provide equal presentation of the financial statements of non-profit organizations with the aim to be easy to understand, have relevance, be accountable and have high appeal in the long run. The approach used is qualitative method that is observation, interview or review of documents. In this study, researchers conducted direct interviews into the field to get the required data in accordance with the desired purpose and establish a good relationship between researchers and informants, namely the Manager of the Asy-Syuhada Mosque in Pamekasan to find out about the accountability of financial management of the Bina Umat Al-Mu’thi Orphanage Foundation. The results of this study are with the availability of financial statements in accordance with PSAK No. 45 of the Asy-Syuhada Mosque has accountable financial information to be presented to the public.